Pilgrimage and Pilgrim Hierarchies in Vernacular Discourse: Comparative Notes from the Camino de Santiago and Glastonbury - Tiina Sepp (Journal of Ethnology and Folkloristics)
This article is based on my fieldwork conducted in two important destinations in the spiritual landscape of European vernacular religion – the Camino de Santiago (pilgrimage route to Santiago de Compostela) in northern Spain, and Glastonbury in southwest England. In this comparison between modern expressions of pilgrimage, I look into the power relationships that exist on the pilgrimage, describe how hierarchies of pilgrims are created and maintained, and reflect on the meaning of the words pilgrim and pilgrimage. The co-existence of the different belief systems of Christianity and New Age and the conflicts and tension between them will be explored. I will also examine discourse around competing male and female energies.